Parkinsonism and distinct dementia patterns in a family with the MAPT R406W mutation. Issue 3 (3rd June 2013) - Carney, Regina M.; Kohli, Martin A.; Kunkle, Brian W.; Naj, Adam C.; Gilbert, John R.; Züchner, Stephan; Pericak‐Vance, Margaret A.
Abstract: Background: The Arg406Trp (R406W) missense mutation in the microtubule‐associated protein‐tau gene (MAPT ) is a known cause of early‐onset dementia. Various dementia phenotypes have been described, including frontotemporal dementia (FTD), FTD with parkinsonism, and early‐onset Alzheimer disease (EOAD)‐like presentations. Methods: Using whole‐exome capture with subsequent sequencing, we identified the R406W mutation in a family with multiple individuals with clinically diagnosed EOAD, in a pattern suggesting autosomal dominant inheritance. We reevaluated all available family members clinically. Results: Each of the affected individuals had a course meeting clinical criteria for EOAD. Two distinct disease trajectories were apparent: one rapidly progressive, and the other long and gradual. Four of five affected individuals also manifested parkinsonian symptoms. FTD features were not prominent and, when present, appeared only late in the course of dementia. Conclusions: The MAPT R406W mutation is associated with EOAD‐like symptoms and parkinsonism without FTD, as well as distinct cognitive courses.